Employee Engagement Among Business Process Outsourcing Industries in a Freeport Zone Amidst the Pandemic - Hans Christian U Mondejar; John Mark R Asio (Research Synergy Foundation, 2023)
Employee engagement emerged as one of the most important topics for HR managers and practitioners in the industry. This study aims to analyze and assess how various organizations engaged their workers throughout the coronavirus epidemic. The Philippine Business Process Outsourcing (BPO) companies have shifted remote work set-up to ensure productivity. The researchers focused on 100 purposively selected managers and team leaders of BPO companies in a particular freeport zone in the Philippines. The proponents utilized a descriptive-correlation research design with the help of a modified survey instrument. Statistical analyses used were mean and Pearson-r moment of correlation with the help of SPSS 20. Results show that the respondents gave the study a remark of